Teachers' and students' perceptions of oral communicative activities in a Libyan EFL classroom - Rema Alkilani; Paramaswari Jaganathan; Sabariah Abd Rahimi (MEXTESOL Journal publishes, 2025)
Oral communicative activities (OCA) play a significant role in the English learning and teaching process due to its positive effects on improving speaking skills. However, not all English language teachers and learners have adequate knowledge about these activities. In some countries, like Libya, teachers focus more on silent individual learning rather than emphasizing the importance of communicative activities. Therefore, the current study focuses on students' and teachers' perceptions of OCA in English in special Libyan schools based in Malaysia. This is a preliminary study reliable for our future full-scale research study. A mixed method approach was applied in the study where first, participating students filled out questionnaires, followed by interviews with the teachers, and a focus group interview with students to discover their perceptions of OCA and to explore their understanding, its relevance and possible use in the EFL classes. The findings showed that both teachers and students considered OCA crucial in developing oral language proficiency, but participating students had limited knowledge of OCA in their classrooms. This study is significant in providing insights to the Libyan teachers and students on how OCA is essential in maximizing their speaking skills, and it should be implemented in a language class.